2014
DOI: 10.4137/bbi.s13649
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Dengue Virus MicroRNA-Like Structures and Their Cellular Targets

Abstract: MicroRNAs (miRNAs) are small, noncoding RNA molecules that regulate transcriptional and posttranscriptional gene regulation of the cell. Experimental evidence shows that miRNAs have a direct role in different cellular processes, such as immune function, apoptosis, and tumorigenesis. In a viral infection context, miRNAs have been connected with the interplay between host and pathogen, occupying a major role in pathogenesis. While numerous viral miRNAs from DNA viruses have been identified, characterization of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…The program slides a window of defined size across the entire sequence of interest, advancing each window by a given step size . The parameters of window and step sizes were set at 500 and 1 nt, respectively, as described in other literature . The secondary structures of the RNAs corresponding to each window were predicted using the RNAFold algorithm .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The program slides a window of defined size across the entire sequence of interest, advancing each window by a given step size . The parameters of window and step sizes were set at 500 and 1 nt, respectively, as described in other literature . The secondary structures of the RNAs corresponding to each window were predicted using the RNAFold algorithm .…”
Section: Methodsmentioning
confidence: 99%
“…While the regulatory function of miRNAs is well documented in eukaryotes, there have not been many reports on virally encoded miRNAs, with preliminary reports identifying miRNAs in herpes simplex virus type 1, human adenovirus, dengue virus, West Nile virus, porcine reproductive and respiratory syndrome virus, and human cytomegalovirus …”
Section: Introductionmentioning
confidence: 99%
“…The geographical location of KFDV is not just limited to India, genome analysis studies has shown that it has more than 90 % sequence identity with Alkhurma hemorrhagic fever virus (AHFV), which is isolated in 1994 from blood of hemorrhagic fever patients in Makkah, Saudi Arabia and thought to be transferred by migratory birds from India [15,16]. Many members of Flaviviridae family such as Dengue [17], Japanese Encephalitis [18], and recently Zika virus [19] were predicted to have encoded miRNAs. It is also evident in past that viral miRNAs can down regulate host genes expression [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…To date, RNA virus-encoded miRNAs have been identified in Hepatitis C virus [15], Human Immunodeficiency virus (HIV) [16], Bovine Leukemia virus (BLV) [17], West Nile virus (WNV) [18], Dengue virus(DENV) [19] and Middle East Respiratory Syndrome (MERS) coronavirus [20]. Very recent studies revealed that the antigenome of another cytoplasmic RNA virus, Hepatitis A virus (HAV), could be processed into miRNA-like small RNAs by the cellular miRNA processing machinery, similar to virus genomes [21].…”
Section: Introductionmentioning
confidence: 99%